PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN CUSTOMER GEN Z PADA COFFE SHOP POINT COFFE BANDAR LAMPUNG: THE INFLUENCE OF SERVICE QUALITY ON GEN Z CUSTOMER SATISFACTION AT COFFEE SHOP POINT COFFEE BANDAR LAMPUNG - Abdillah, Satria Yuda; Ruslaini; Heri Sutopo (Program Studi Ekonomi Syariah, 2025)
This study aims to analyze the effect of service quality on customer satisfaction among Generation Z at one of the coffee shops in Bandar Lampung, namely Point Coffee. The background of this research is based on the growing trend of Generation Z’s interest in coffee shops as part of a modern lifestyle. The research employed a quantitative approach using a survey method. Data were collected through an online questionnaire distributed to 100 respondents who are Generation Z consumers that have used the services of Point Coffee Bandar Lampung. The sampling technique used was purposive sampling to ensure that respondents met the research criteria. The results of the analysis show that service quality has a positive and significant effect on customer satisfaction. This is evidenced by the t-count value of 9.560, which is greater than the t-table value of 1.984, and a significance level of 0.000, which is less than 0.05. Furthermore, the relationship between the variables is categorized as strong, with a correlation coefficient of 0.695. Service quality contributes 48.3% to customer satisfaction, while the remaining percentage is influenced by other factors not examined in this study. These findings provide important implications for coffee shop management in formulating effective service strategies to attract and retain Generation Z customers. Thus, improving service quality is a key strategy to enhance customer satisfaction in the increasingly competitive coffee shop industry